Etyka zawodowa w rachunkowości - Garstka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2014)
Recently we have observed the high volatility and complexity of law and business transactions, as well as the assumption of prepared valuations and self-shaping principles in accounting. Greater independence in a changing environment increases the risk of unethical behaviour. There have been many cases of negative behaviour in accounting, known as a creative, aggressive or fraudulent accounting. Responsibility for bankruptcy and financial failures was pinned on accounting, which shattered the reputation of the accountants concerned. Professional requirements for accountants are high and they have greatly increased, especially in the financial operations sector. However, it is expected that employees will also act ethically. Professionalism is associated in the same way with professional competence and ethical standards. The Code of Professional Ethics in Accounting introduces important ethical principles for accountants. It is worth noticing how the principles refer to human traits, virtues and considering whether to accept and obeying them as an act of conscience. Accountants are facing ethical dilemmas that affect their private life.